Tackling Inadequate Pharmaceutical Services in Africa: Options for Public Health Action - Babatunde Omilola; N’doh A. Sanogo (Public Health, 2020)
The present document aims to present challenges and opportunities to support pharmaceutical industry in Africa. The proliferation of fake medicines in the continent is a major public health problem, with a global market worth roughly US $200 billion and sub-Saharan Africa accounts for around 42% of the world’s cases (21% for north African and the middle East).1,2 We will first discuss the challenges for the continent in the fight against counterfeit medicines and finally the challenges and opportunities to support pharmaceutical industry in Africa.